2017
DOI: 10.1371/journal.pone.0177389
|View full text |Cite
|
Sign up to set email alerts
|

Proteome dynamics of cold-acclimating Rhododendron species contrasting in their freezing tolerance and thermonasty behavior

Abstract: To gain a better understanding of cold acclimation in rhododendron and in woody perennials in general, we used the 2D-DIGE technique to analyze the rhododendron proteome during the seasonal development of freezing tolerance. We selected two species varying in their cold acclimation ability as well as their thermonasty response (folding of leaves in response to low temperature). Proteins were extracted from leaves of non-acclimated (NA) and cold acclimated (CA) plants of the hardier thermonastic species, R. cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
4
5
0
Order By: Relevance
“…A similar quantitative profile was also verified for over-representation of cytosolic aldehyde dehydrogenase ALDH7B4 (AT1G54100) (Supplementary Table S3 and Supplementary Figure S5G), which is induced in plants as result of various abiotic stress conditions (Stiti et al, 2011). Measured level of specific proteins mentioned above was in good agreement with that observed in kiwifruit exposed to cold storage under different experimental conditions (Minas et al, 2016), in other climacteric fruits during ripening or cold storage (Nilo et al, 2010; Zhang et al, 2011; Giraldo et al, 2012; Zheng et al, 2013; Li et al, 2015; Du et al, 2016; Wu et al, 2016; Tanou et al, 2017) and in plants exposed to cold stress (Janmohammadi et al, 2015; Die et al, 2016, 2017). Some of the above-mentioned antioxidant proteins occurred in the interaction network shown in Figure 5.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…A similar quantitative profile was also verified for over-representation of cytosolic aldehyde dehydrogenase ALDH7B4 (AT1G54100) (Supplementary Table S3 and Supplementary Figure S5G), which is induced in plants as result of various abiotic stress conditions (Stiti et al, 2011). Measured level of specific proteins mentioned above was in good agreement with that observed in kiwifruit exposed to cold storage under different experimental conditions (Minas et al, 2016), in other climacteric fruits during ripening or cold storage (Nilo et al, 2010; Zhang et al, 2011; Giraldo et al, 2012; Zheng et al, 2013; Li et al, 2015; Du et al, 2016; Wu et al, 2016; Tanou et al, 2017) and in plants exposed to cold stress (Janmohammadi et al, 2015; Die et al, 2016, 2017). Some of the above-mentioned antioxidant proteins occurred in the interaction network shown in Figure 5.…”
Section: Resultssupporting
confidence: 85%
“…In the whole, the quantitative behavior of specific proteins involved in glycolysis, the Krebs cycle, alcoholic fermentation, energy production and additional carbon metabolism pathways in kiwifruit well paralleled that observed in the same fruit exposed to low temperatures but in different experimental setup (Minas et al, 2016; Asiche et al, 2018), in other fruits during ripening (Borsani et al, 2009; Andrade et al, 2012; Huerta-Ocampo et al, 2012; Nogueira et al, 2012; Yun et al, 2013; Zheng et al, 2013; Du et al, 2016; Xiao et al, 2018) or cold-based postharvest management (Nilo et al, 2010; Li et al, 2015; Wu et al, 2016; Tanou et al, 2017; Wang et al, 2017), or in other plants experiencing cold stress conditions (Janmohammadi et al, 2015; Die et al, 2016, 2017), suggesting the existence of common regulation mechanisms of these metabolic pathways in above-mentioned organisms. Most of the proteins reported above constitute two functional subnetworks linked to each other and to additional ones related to stress response and protein destination/storage (Figure 5).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Overexpression of the GCSH gene resulted in an increase in photosynthesis and biomass in Arabidopsis thaliana [ 56 ]. A previous study reported that the abundance of GS in cold-tolerant rhododendrons was higher than in cold-sensitive varieties [ 57 ]. A study on rice anthers found that GCSH was up-accumulated in the cold-sensitive variety, but did not significantly change in the cold-tolerant cultivar after cold stress [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A genetic analysis of the British population of R. ponticum has confirmed the presence of genes from R. catawbiense (Michx), suggesting past hybridization between the two species. R. catawbiense is a species native to North America and characterized by greater cold tolerance (Erfmeier et al, 2011 ; Snowdonia Rhododendron Partnership, 2015 ; Die et al, 2017 ), a trait that may increase invasiveness of R. ponticum in the UK. However, an in-depth analysis is still required to identify the other key environmental factors responsible for colonization and spread of this species.…”
Section: Introductionmentioning
confidence: 99%